(untitled) (Medico Legal Update, 2020)
Scabies is a common parasitic infection, caused by sarco-sarcoptes, the infection occurs when the Sarcoptes penetrates the corneal layer of the skin, predominant pathological manifestations, through inflammatory and allergic reactions to mite products.This study is designed to obtain the Evaluation of the immune response in scabies patient (Ordinary and Prisoners) treated with Permethrin 5%.The study included (28)Ordinary Scabies patients, (32) prisonersas well as a (30)healthy person as a control group. Blood samples were collected from all studied groups Enzyme-linked immunosorbent assay (ELISA) was used to measure Interleukine-4,IL-9 and total IgE.Results of the study showed that serum,IL-4 showed a significant (P?0. 0001) increasing in prisoners compared to ordinary patients and control groups(248.8±19.3vs.79.2±10.7pg/ ml),(248.8±19.3vs.73.9±5.5pg/ml)respectively,while IL-9 showed a significant (P? 0.001), increasing in control compared to Ordinary Scabies patients group and prisoners (506.9±48.7vs.337.8±18.2 pg/ml), (506.9±48.7 vs. 424.1±36.5 pg/ml) respectively in post- treatment, There was positive correlation between (IL-4 and IgE).Levels of two cytokines (IL-4, and IL-9) were assessed in sera of Ordinary ScabiesPatients and control group, IL-4 showed a significant (P?0. 0001) increasing in Ordinary Scabies comparedto control group (92.5±7.0 vs. 73.9 ± 5.5pg/ml), respectively. While IL-9with asignificant decreasinglevel inOrdinary Scabies patients compared to control group(97.8 ±18.8 vs. 506.9 ±48.7 pg/ml) in pre-treatment, level of IgE were recorded in pre- treatment in ordinary patients and prisoners (314.8±37.5 vs. 17.8±3.7 IU/ml), (372.7±37.5 vs. 17.8±3.7 IU/ml) respectively, were a significantly increasing (P=>0.05) as compared to healthy control. In post- treatment IgE levels show a significantly lowering (P=>0.05), in prisoners than Ordinary patients(14.5±1.7 vs. 33.3±2.4 IU/ml).